DESAIN POWER MONITORING SYSTEM USING WIRELESS TECHNOLOGY - Diana Alia; Henna Nurdiansari; Edi Kurniawan; Renta Novaliana Siahaan; Hilmi Wiko (Jurnal Maritim Malahayati, 2023)
Energy is one of the most interesting topics from various aspects. The issue of energy saving is one of the most interesting researched topics. Energy management is one way to save energy. In energy management, it is necessary to monitor the power of electrical equipment to find out when and where electrical energy is being spent. Power monitoring system is designed to monitor electrical parameters such as power, current, and voltage of several household appliances. Electrical parameters on household appliances could be detected by using them. electrical parameters on household appliances and a Bylink application that can connect sensor data with android applications. By using aplication, user could monitor electrical parameters can make it easier for users to monitor electrical parameters. This prototype system, has been made, has tested and compared with the electrical parameters that exist in the specifications of household appliances. The error that occurs in this tool is 0.80% for the voltage parameter and 1.49% for the current parameter.